2019
DOI: 10.1259/bjr.20190045
|View full text |Cite
|
Sign up to set email alerts
|

MRI evaluation of pelvis in Mayer–Rokitansky–Kuster–Hauser syndrome: interobserver agreement for surgically relevant structures

Abstract: The paired Mullerian or paramesonephric ducts fuse between 6 and 11 weeks of gestation to form uterus, cervix and upper two-thirds of vagina. Mullerian duct anomalies (MDA) result from disruption in any of the three stages of uterine development, i.e. organogenesis, fusion or septal resorption. 1 Ovaries develop from primordial germ cells, while lower one-third of vagina develops from sinovaginal bulb. Owing to the different embryological origins, ovaries and lower third of vagina are not involved in MDA. 2 Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 22 publications
(68 reference statements)
3
12
0
1
Order By: Relevance
“…1), with isointense signals at the T2WI sequence frequently occurring among these subjects. This discovery aligned with a prior study by Bhayana (2019), who stipulated that the right and left uterine buds, according to the craniocaudal position to the ovarium, are mainly situated at the caudal site; in consonance with the anterior position, they occur most often at the anterior site.…”
Section: Uterine Budssupporting
confidence: 86%
See 4 more Smart Citations
“…1), with isointense signals at the T2WI sequence frequently occurring among these subjects. This discovery aligned with a prior study by Bhayana (2019), who stipulated that the right and left uterine buds, according to the craniocaudal position to the ovarium, are mainly situated at the caudal site; in consonance with the anterior position, they occur most often at the anterior site.…”
Section: Uterine Budssupporting
confidence: 86%
“…3a). This result was discordant with a previous study by Bhayana (2019), in which 13 subjects out of 18 appeared hyperintense and five patients hypointense at the T2WI sequence. 4.4 Ovarium Our study result showed that both right and left ovaries were evident in 35 patients (92.1%), all positioned within intrapelvic (Fig.…”
Section: Midline Triangular Soft Tissuesupporting
confidence: 68%
See 3 more Smart Citations